Immune responses and histopathological changes in rabbits immunized with inactivated SARS coronavirus - Zhang, Chuan-hai (Virol Sin, 2008)
To evaluate the immunogenicity of inactivated SARS coronavirus (SARS-CoV), three groups of rabbits were immunized three times at 2-week intervals with inactivated vaccine + adjuvant, adjuvant, and normal saline respectively. Eight batchs of serum were sampled from the auricular vein at day 7 to day 51, and specific IgG antibody titers and neutralizing antibody titers were detected by indirect ELISA and micro-cytopathic effect neutralizing test. Antibody specificity was identified by proteinchip assay. Histopathological changes were detected by H&E staining. The results showed that, rabbits in the experimental group immunized with inactivated SARS-CoV all generated specific IgG antibodies with neutralizing activity, which suggested the inactivated SARS-CoV could preserve its antigenicity well and elicit an effective humoral immune responses. The peak titer value of specific IgG antibody and neutralizing antibody reached 1:40960 and 1:2560 respectively. In the experimental group, no obvious histopathological changes was detected in the H&E stained slides of heart, spleen, kidney and testis samples, but the livers had slight histopathological changes, and the lungs presented remarkable histopathological changes. These findings are of importance for SARS-CoV inactivated vaccine development.